Associations of maternal BMI and gestational weight gain with neonatal adiposity in the Healthy Start study. Issue 2 (3rd December 2014) - Starling, Anne P; Brinton, John T; Glueck, Deborah H; Shapiro, Allison L; Harrod, Curtis S; Lynch, Anne M; Siega-Riz, Anna Maria; Dabelea, Dana
ABSTRACT: Background: Maternal obesity and weight gain during pregnancy are risk factors for child obesity. Associations may be attributable to causal effects of the intrauterine environment or genetic and postnatal environmental factors. Objective: We estimated associations of maternal prepregnancy body mass index (BMI) and gestational weight gain (GWG) overall and in early pregnancy, midpregnancy, and late pregnancy with neonatal adiposity. Design: Participants were 826 women enrolled in a Colorado prebirth cohort who delivered term infants (2010–2013). GWG to 39 wk of gestation was predicted by using mixed models, and early pregnancy, midpregnancy, and late pregnancy rates of GWG (0–17, 17–27, and 27 wk to delivery) were calculated from repeated weight measures. Neonatal body composition was measured by using air-displacement plethysmography ≤3 d after birth. Results: Each1-kg/m 2 increase in maternal BMI was associated with increased neonatal fat mass (5.2 g; 95% CI: 3.5, 6.9 g), fat-free mass (7.7 g; 95% CI: 4.5, 10.9 g), and percentage of body fat (0.12%; 95% CI: 0.08%, 0.16%). Each 0.1-kg/wk increase in predicted GWG was associated with increased fat mass (24.0 g; 95% CI: 17.4, 30.5 g), fat-free mass (34.0 g; 95% CI: 21.4, 46.6 g), and percentage of body fat (0.55%; 95% CI: 0.37%, 0.72%). No interaction was detected between BMI and GWG in their effects on neonatal body composition. Early pregnancy, midpregnancy, and late pregnancy rates of GWG were independently associated with fat mass and percentage of body fat. Midpregnancy and late pregnancy GWGs were associated with fat-free mass. An observed GWG that exceeded recommendations was associated with higher neonatal fat mass and fat-free mass but not percentage of body fat relative to adequate GWG. Conclusions: Maternal prepregnancy BMI and GWG, including period-specific GWG, were positively and independently associated with neonatal adiposity. Associations of early and midpregnancy weight gain with neonatal adiposity support the hypothesis that greater maternal weight gain during pregnancy, regardless of prepregnancy BMI, is directly related to offspring adiposity at birth. The Healthy Start study was registered as an observational study at clinicaltrials.gov as NCT02273297.